Effectiveness Of Hybrid/Blended Learning On Material Understanding In Practical Courses - Mellasanti Ayuwardani; Sri Eka Sadriatwati; Rara Ririn Budi Utaminingtyas; Rustono, Rustono (International Journal of Education, Vocational and Social Science, 2023)
The development of technology that is entering the industrial era 5.0 plus the covid-19 pandemic which has turned into an ongoing covid-19 endemic, makes the use of technology very much needed. When the endemic announcement began, all face-to-face activities in the world of education gradually began to run, but with restrictions on activities and class capacity, including practicum lectures. The problem of this research is "How the Effect of Hybrid/Blended Learning Effectiveness on Material Understanding in the typing basics practice course of the Business Administration Department of Semarang State Polytechnic". The purpose of this research is the development of a conceptual integration model of Hybrid/Blended Learning Effectiveness, Material Understanding. The sample size of this study was 89 respondents. The data collection method is done by providing a list of questions using Google Form. The t test results show that the Hybrid/Blended Learning Effectiveness variable has a t value of 10.263> t table 1.666 with a significance value of 0.000 <0.05, with an Adjusted R Square value of 0.542 or 54.2%. The conclusion in this study is that there is a positive and significant influence between the Effectiveness of Hybrid/Blended Learning on Material Understanding with an influence of 54.2%.